К вопросу концептуализации бинарных оппозиций и «противоречий» в семиотике литературы Ю. М. Лотмана - Кроо , Каталин (SlavVaria, 2022)
Lotman and Gukovsky. Dialogue in the historical and cultural context. Article 1) provides a chronological overview of Y. M. Lotman's reviews of G. A. Gukovsky's ideas and teaching activities: from the pre-war and post-war time of study to the latest memoir texts; 2) the most significant plots of Lot-man's polemic with Gukovsky's historical and literary concepts are considered in the field of history of Russian literature; 3) fragments of Lotman's un-published lectures from 1960 are introduced into scientific field as they became the basis of his first monograph in the field of structural poetics. These lectures testify to the strong influence of Gukovsky's ideas about the unity of content and form in works of art on Lotman's structuralist theory.